Fatty acid composition of five Malaysian biscuits (cream crackers) with special reference to trans-fatty acids - Neo, Yun Ping; Tan, Cheng Huat; Ariffin, Abdul Azis (Universiti Putra Malaysia Press, 2007)
The fatty acid composition and trans fatty acids (TFA) contents of samples of five Malaysian cream crackers biscuit brands were determined by gas-liquid chromatography, using a 60 m Supelco SP2340 fused silica capillary column and flame ionization detection. The identities of the fatty acids were established by comparing their retention times with authentic standards from Supelco. The results were expressed as relative percentages. The total saturated fatty acids (SFA) in the samples ranged from 48.90% to 54.87% of total fatty acids. As for the polyunsaturated fatty acids (PUFA), the total PUFA in the samples ranged from 9.97% to 11.73% of total fatty acids. Total trans fatty acids (TFA) ranged from 0.17% to 0.77% of total fatty acids. The monotrans 18:2 tc or 18:2 ct isomer content ranged from 0.07% to 0.10% of total fatty acids and the ditrans 18:2 isomer (9t, 12t) was not detected. The results indicate that all the fat sources of the 5 sample crackers biscuit brands were palm oil based.